Patients’ Experience of Myositis and Further Validation of a Myositis-specific Patient Reported Outcome Measure - Establishing Core Domains and Expanding Patient Input on Clinical Assessment in Myositis. Report from OMERACT 12 - Regardt, M.; Basharat, P.; Christopher-Stine, L.; Sarver, C.; Bjorn, A.; Lundberg, I. E.; Wook Song, Y.; Bingham, C. O.; Alexanderson, H. (J Rheumatol, 2015)
OBJECTIVE: The Outcome Measures in Rheumatology (OMERACT) myositis working group was established to examine patient-reported outcomes (PRO) as well as to validate patient-reported outcome measures (PROM) in myositis. METHODS: Qualitative studies using focus group interviews and cognitive debriefing of the myositis-specific Myositis Activities Profile (MAP) were used to explore the experience of adults living with polymyositis (PM) and dermatomyositis (DM). RESULTS: Preliminary results underscore the importance of patient input in the development of PROM to ensure content validity. Results from multicenter focus groups indicate the range of symptoms experienced including pain, fatigue, and impaired cognitive function, which are not currently assessed in myositis. Preliminary cognitive debriefing of the MAP indicated that while content was deemed relevant and important, several activities were not included; and that questionnaire construction and wording may benefit from revision. A research agenda was developed to continue work toward optimizing PRO assessment in myositis with 2 work streams. The first would continue to conduct and analyze focus groups until saturation in the thematic analysis was achieved to develop a framework that encompassed the patient-relevant aspects of myositis. The second would continue cognitive debriefing of the MAP to identify potential areas for revision. There was agreement that further work would be needed for inclusion body myositis and juvenile dermatomyositis, and that the inclusion of additional contributors such as caregivers and individuals from the pharmaceutical/regulatory spheres would be desirable. CONCLUSIONS: The currently used PROM do not assess symptoms or the effects of disease that are most important to patients; this emphasizes the necessity of patient involvement. Our work provides concrete examples for PRO identification.